Use of First Aid Equipment for Early Treatment of Accident Victims: A review - Yusriani, Yusriani; Burhanuddin, Nurfardiansyah; Anwar, Muhammad Qayyum Aisy; Alfatirah, Shoofiyah; Azizah, Maudi Nailah; Ulfia, Nurul Adha; Ramdhany R, Noer Azhisya; Acob, Joel Rey U. (Journal of Health Science and Medical Therapy, 2025)
First aid is an important initial action in the treatment of sudden injury or illness before getting further medical assistance. First aid kit (Pertolongan Pertama Pada Kecelakaan) is one of the important tools in emergency treatment in various situations. This study aims to describe the use of first aid kits in first aid situations in various environments. This study uses a purposive sampling method, where respondents are selected based on certain criteria, such as experience using first aid kits in emergency conditions. Data was collected through questionnaires and interviews to determine the frequency, effectiveness, and obstacles encountered in the use of first aid kits. The results showed that although most respondents understood the importance of first aid kits, there were variations in knowledge and skills in their use. Factors such as the availability of first aid kits and understanding of them affect the effectiveness of first aid. Therefore, further education on the use of the first aid kit and maintenance of the contents of the kit is needed to improve preparedness in emergency situations.